Peran Work Overload, Work Environment, Work Family Conflict & Work Stress Terhadap Job Performance - Diana Damayanti; Santi Rimadias; Marissa Grace Haque; Denok Sunarsi; Kosasih Kosasih; Raden Roro Vemmi Kesumadewi (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this research is to identify the role of Work overload, work environment, work-family conflict and work stress on job performance in Public Facilities and Infrastructure Handling Officers on South Jakarta. The sample used in the study was 130 respondents of Public Facilities and Infrastructure Handling Officers on Jakarta. The data collection techniques in this research used primary data by distributing questionnaires to Public Infrastructure and Facilities Handling Officers in Jakarta with data collected by 130 respondents using Structural Equation Modeling (SEM) analysis supported by SPSS 24 and AMOS 21. The results of this study indicate that 1) Work overload has a positive and significant effect on Job Stress. 2) Work Environment has a negative and significant effect on Job Stress. 3) Work Environment has no influence on Job Performance. 4) Work Environment has no influence on Job Performance. 5) Work Stress has no effect on Job Performance. 6) Work-Family Conflict has no effect on Job Performance. 7) Work Stress is proven to be a variable that intervenes between Work Overload and Job Performance. 8) Work Stress is proven to be a variable that intervenes between Work Environment and Job Performance.